2021
DOI: 10.1007/s00431-021-04001-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography correlated to four different histological fibrosis scores in children with liver disease

Abstract: Currently, liver histology is the gold standard for the detection of liver fibrosis. In recent years, new methods such as transient elastography (TE) have been introduced into clinical practice, which allow a non-invasive assessment of liver fibrosis. The aim of the present study was to investigate the predictive value of TE for higher grade fibrosis and whether there is any relevance which histologic score is used for matching. For this purpose, we compared TE with 4 different histologic scores in pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…These findings are comparable to a recent study that assessed FibroScan LSM and histologic fibrosis stages in a cohort of 80 pediatric patients. [ 16 ] Importantly in our study, the strongest correlations and predictive ability were found in the non‐NAFLD group. This finding may be due in part to the limitations of the NAFLD cohort as no participants with NAFLD in our study had severe histologic fibrosis (Ishak 5–6; METAVIR F4), which may have impacted our ability to discriminate between low‐ and high‐fibrosis stages.…”
Section: Discussionmentioning
confidence: 45%
“…These findings are comparable to a recent study that assessed FibroScan LSM and histologic fibrosis stages in a cohort of 80 pediatric patients. [ 16 ] Importantly in our study, the strongest correlations and predictive ability were found in the non‐NAFLD group. This finding may be due in part to the limitations of the NAFLD cohort as no participants with NAFLD in our study had severe histologic fibrosis (Ishak 5–6; METAVIR F4), which may have impacted our ability to discriminate between low‐ and high‐fibrosis stages.…”
Section: Discussionmentioning
confidence: 45%
“…The remaining 106 studies underwent full-text article review and a total of 52 studies were excluded as they did not assess the diagnostic accuracy of advanced ultrasound imaging techniques but focused on the conventional grayscale ultrasound and Doppler techniques, where parameters such as gallbladder abnormalities, triangular cord sign, and the presence or absence of hepatic subcapsular flow on color Doppler ultrasound were assessed as predictor variables in the diagnosis of BA. A total of eight studies that were excluded during the full article review, which assessed the diagnostic performance of the advanced ultrasonography technique of SWE, not for the preoperative diagnosis of BA but the preoperative diagnosis of hepatic fibrosis in children with BA [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], whereas one study assessed the preoperative diagnostic accuracy of 2D SWE for liver cirrhosis in BA patients [ 55 ]. The other excluded studies focused on the diagnosis of liver fibrosis among post-operative BA children using elastography techniques [ 54 ], whereas two studies were excluded due to wrong outcomes as they evaluated the accuracy of the elastography techniques in the diagnosis of liver fibrosis, and this was for participants outside the specified age-range of the present study, which focused on infants below 1 year of age [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of eight studies that were excluded during the full article review, which assessed the diagnostic performance of the advanced ultrasonography technique of SWE, not for the preoperative diagnosis of BA but the preoperative diagnosis of hepatic fibrosis in children with BA [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], whereas one study assessed the preoperative diagnostic accuracy of 2D SWE for liver cirrhosis in BA patients [ 55 ]. The other excluded studies focused on the diagnosis of liver fibrosis among post-operative BA children using elastography techniques [ 54 ], whereas two studies were excluded due to wrong outcomes as they evaluated the accuracy of the elastography techniques in the diagnosis of liver fibrosis, and this was for participants outside the specified age-range of the present study, which focused on infants below 1 year of age [ 56 , 57 ]. A study by Zhou et al [ 58 ] that utilized an ensembled deep learning model, which was reported to surpass human expertise in the diagnosis of BA, was, however, excluded from the study, as the model was based on conventional sonographic gallbladder images.…”
Section: Resultsmentioning
confidence: 99%
“…LSM was categorized using previously described liver biopsy supported thresholds derived from children with cholestatic or chronic liver diseases and a meta‐analysis–derived reference range for normal liver stiffness in healthy children 20,21,24–28. For analyses, the following categories were applied: <6 kPa (no or mild fibrosis, F0/F1), 6–10 kPa (significant fibrosis, ≥F2), 10–15 kPa (bridging fibrosis, F3/4), and 15–75 kPa (cirrhosis, F4).…”
Section: Participants and Methodsmentioning
confidence: 99%